DAMPAK PENDIRIAN ALFAMART TERHADAP KURANGNYA PENDAPATAN TOKO KECIL DIKELURAHAN TALANG BABAT KECAMATAN MUARA SABAK BARAT (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to find out the impact on the community of small shop owners as a result of the establishment of an Alfamart in Talang Babat Village, Muara Sabak Barat District, this research is of a qualitative type using primary and secondary data sources. The object of this research is a number of small shop owners who feel the impact of the establishment of an alfamart in Talang Babat Village, Muara Sabak Barat District. Data were obtained directly from 15 respondents using data analysis methods, namely observation, interviews and personal documentation, then the data was processed using data processing techniques. The results of the study show that: The negative impact is felt, especially losing a lot of their regular customers and then decreasing their daily turnover or income which causes them to have to rethink or increase capital for tomorrow. However, this cannot be separated from the positive impact that is felt, namely being able to provide easy access to the whole community and being able to provide jobs for young people and women in the Talang Babat village. Before the existence of Alfamart, their income could be said to be decent or sufficient, but now it is no longer the case. It is clear that the existence of Alfamart greatly influenced the sustainability of small shops. Traders admit that for the last few years, Alfamart has had quite a pronounced impact. Their income is also decreasing as felt by some informants, namely by 40% per day.